The reproductive biology of mangrove crab (Neosarmatium smithi) in Xuan Thuy National Park, Nam Dinh, Vietnam - Lai, Duy Phuong; Do, Manh Dung; Luu, Xuan Hoa; Nguyen, Xuan Thanh (Vietnam Journal of Marine Science and Technology, 2025)
The results of the analysis of 458 samples of mangrove crab (Neosarmatium smithi) collected in areas where mangrove crab is distributed in the tidal zone with mangrove forests in Xuan Thuy Nam Dinh National Park from October 2022 to September 2023 showed that the spawning season of mangrove crab is from mid - April to early September, and is concentrated from early June to early August. In all months, the ratio of females to males is always dominant. The female/male ratio in the mangrove crab population averages 1.36 and ranges from 1.25–1.46. The onset of sexual maturity occurs when the carapace width (CW) of females exceeds 21 mm and that of males exceeds 24 mm. Absolute fecundity (Fa) ranged from 17,580–25,733 eggs/individual, averaging 21,571 eggs/individual. The larvae of the mangrove crab develop from zoea larvae with 5 sub - stages, and megalop larvae with 3 sub - stages. Our findings contribute information to the planning of the artificial seed production, conservation and sustainable development of the mangrove crab native resource.